Three joint temperament-character configurations account for learning, personality and well-being: normative demographic findings in a representative national population - Moreira, Paulo A. S.; Inman, Richard A.; Cloninger, C. Robert (Frontiers in Psychology, 2023)
A common practice in research and clinical practice is to use data considered representative of a target population to compare and understand the personality characteristics of specific groups or specific individuals. To this end, numerous studies have presented normative data for the temperament and character traits outlined in Cloninger’s psychobiological model of personality. However, recent genomic evidence demonstrates that human personality is organized as a complex hierarchy that ascends beyond the individual traits to multi-trait profiles that regulate emotional reactivity (temperament profiles) or goals and values (character profiles), and then to three phenotypic networks, which integrate temperament profiles and character profiles, that regulate learning. Given this recent understanding, our aim was to provide a novel and more comprehensive description of personality features at a societal level (using a stratified sample representative of the Portuguese population) by considering personality at its higher levels of complexity. Toward this goal, a stratified sample of 2,443 Portuguese adults responded to the Revised Temperament and Character Inventory (TCI-R). We summarize the prevalence of (a) temperament profiles, (b) character profiles, and (c) integrated temperament-character networks within the whole sample, as well as for men vs. women and different age groups separately. Independent of age and education, women were more likely to be capable of resourceful productivity and helpful cooperation combined with being more intuitive, meditative and creative than men. Independent of age and gender, individuals with a degree were also more likely to present these biopsychosocial features. We also found that the organized character profile was most typical of adults in their 40s. Finally, the distribution of personality profiles across age differed as a function of gender: for men the oldest individuals had the most coherent personalities while high personality integration was most prevalent for women in their 30s.